SENTUHAN PENDIDIKAN PERSPEKTIF GENDER - Darul Ilmi (Universitas Islam Negeri Imam Bonjol Padang, 2013)
Touch of education of gender perspective is a needs today because the children to be a complex scircle. Purpose of this study is to explain what the learning follow children cauntion. Undestanding educational on simultan and holistic, so learning implementation and integration on educational touch. Education to do by teacher should be with humanity, beloving, human relationship oriented to development the children potencial, this pradigm chould be children activity, afectivly, cognitifly and psicomotoric, the minside content to life skill competence, education do not transfers of knowledge, but transfer of value, education is meaningfull of children. Keywords : Touch of education, and gender perspectiveCopyright © 2013 by Kafa`ah All right reservedDOI : 10.15548/jk.v3i2.55